2004
DOI: 10.1152/ajpregu.00453.2003
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of responsive AVP-containing neurons to running stress in the hypothalamus

Abstract: Running becomes a stress, termed running stress, if it persists above the lactate threshold (LT) and results in enhanced plasma ACTH level in humans. Although the exact underlying regulation mechanism is still uncertain, hypothalamic AVP has been shown to play a dominant role in running-induced ACTH release. It is still not known, however, whether running stress activates the hypothalamic AVP-containing neurons that are involved in the activation of the ACTH response. For this reason, we applied our rat runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 47 publications
3
50
1
Order By: Relevance
“…The reason for this discrepancy is unclear at present; however, it is possible that the role of brain PrRP in ACTH release depends upon the type of stress stimuli used. We previously reported that running stress activates AVP neurons in the pPVN and the SON (32). Other previous studies have also shown that AVP, rather than CRH, might play a major role in the facilitation of ACTH release during running (1,38), suggesting that the running stress may differ from other types of stress in which ACTH secretion is mainly regulated by CRH.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The reason for this discrepancy is unclear at present; however, it is possible that the role of brain PrRP in ACTH release depends upon the type of stress stimuli used. We previously reported that running stress activates AVP neurons in the pPVN and the SON (32). Other previous studies have also shown that AVP, rather than CRH, might play a major role in the facilitation of ACTH release during running (1,38), suggesting that the running stress may differ from other types of stress in which ACTH secretion is mainly regulated by CRH.…”
Section: Discussionmentioning
confidence: 90%
“…We previously showed that supra-LT running increased ACTH and blood lactate concentrations, which have been used as indexes of running stress (32,39). The running paradigm was composed of both below-and supra-LT, which are typical exercise intensities that induce different hormonal and metabolic responses to running (44,45), as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence has been reported showing that glutamate affected CRH or AVP at the levels of the ME. Saito et al [32] recently reported that running stress decreased the ME content of AVP and increased in the plasma concentrations of ACTH in male rats, and they suggested that the reduction of the AVP content in the ME might be the result of an increase of AVP release into the portal blood. In the present study, NBQX-induced suppression of ACTH secretion may have been mediated by the inhibition of CRH and AVP release into the portal vein.…”
Section: Discussionmentioning
confidence: 99%